Effects of Acupressure on Pain in Chronic Diseases: A Scoping Review - Hatta, Candra; Handayani, Fitria; Erawati, Meira (Indonesian Journal of Global Health Research, 2024)
Pain is one of them sign the main thing felt by sufferers disease chronic , study handler non- pharmacological pain especially acupressure has Lots carried out, however, review studies are possible used as base thinking intervention This Still limited. Objective from this review is For see effect of acupressure against pain in disease chronic. This review use approach scoping review, with using Pubmed, ScienDirect, Proquest databases with using the keywords “ Acupressure” AND “Pain” AND “Cronic” OR “Cronic diases”. On search the done filtering data with initial filters checklist "free full text", "Publication from 2019-2024", "Randomized Controlled Trial". A review analysis was performed with use approach Arksey and O'Malley theory. The review results show that acupressure has effect positive in reduce and overcome pain in disease chronic, among others reduce painful post operation thoracoscopy and post procedure extracorporeal shock wave lithotripsy (ESWL), then reduce pain in patients cancer , lowering pain in patients coronary angiography , reducing pain in patients hemodialysis , as well reduce pain in patients elderly with osteoarthritis. Study furthermore can do an article review associated with acupressure other methods in overcome symptoms of disease chronic.